Prevalence of asymptomatic carriage of methicillin-resistant Staphylococcus aureus (MRSA) among healthcare workers and its infection control implications: A retrospective observational study. - Nirmala Kumari; Sanjay Kumar; Kumar, Rajesh; Satyendu Sagar (Student’s Journal of Health Research Africa, 2025)
Background In 1961, a year after semisynthetic penicillin was introduced, methicillin-resistant S. aureus (MRSA) isolates were first identified. They are resistant to all penicillin and β-lactam medicines, and this has led to their spread in both hospital and community settings. Objectives Determining the frequency of MRSA colonization among healthcare professionals and evaluating related risk factors were the study’s objectives. Materials and methods It was a retrospective, observational study. The study was carried out at Nalanda Medical College and Hospital (NMCH), Patna, Bihar, India. The study data that was retrieved was for one year, i.e., from February 2023 to January 2024. Data from 220 participants were retrieved for the study. Healthcare professionals working in different intensive care units (ICUs) and high-risk hospital departments, including physicians, nurses, attendants, housekeeping personnel, and technicians, met the study’s inclusion criteria. Results The participants’ average age was 31.4 ± 7.2 years, and 71.3% of them were female. The largest group was made up of nurses (46.4%) and doctors (26.8%). 13.6% of healthcare workers were found to have MRSA carriage. Workers with less education (p = 0.03) and staff nurses (p = 0.002) had considerably higher carriage. The neurosurgical intensive care unit had the greatest percentage of MRSA carriers (13.3%). Gender did not significantly correlate (p = 0.18). Conclusion The study found that MRSA colonization was significantly more common among healthcare workers, with staff nurses and individuals with less education having higher rates. MRSA carrier rates were also greater in certain ICU sites, such as the surgical and neurosurgery ICUs. Recommendations For early detection and prevention, healthcare staff must undergo routine MRSA screening, particularly in high-risk settings like intensive care units.